1998
DOI: 10.1080/135048598354168
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of wage discrimination in professional basketball

Abstract: Previous research has shown that wage discrimination may exist in National Basketball Association (NBA) player salaries. These studies have shown that African-Americans earned from nine to twenty per cent less than whites when on-court performance is held constant. The authors could find no substantial research that has been done in this area since 1991. The present study re-examines this issue. Using salary data from the 1996-97 season and performance statistics from the 1995-96 season, a log-linear wage equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 6 publications
2
29
0
Order By: Relevance
“…Articles by Dey (1997), Gius and Johnson (1998), and Bodvarsson and Brastow (1999) using data from the late 1980s and 1990s failed to find racial wage discrimination. Hamilton (1997) found evidence of racial pay differences only at the upper end of the 1994-1995 season's salary distribution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Articles by Dey (1997), Gius and Johnson (1998), and Bodvarsson and Brastow (1999) using data from the late 1980s and 1990s failed to find racial wage discrimination. Hamilton (1997) found evidence of racial pay differences only at the upper end of the 1994-1995 season's salary distribution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hoang and Rascher (1999) also found evidence of exit discrimination in the 1980s with White players facing 36% less risk of being cut from a team than did Black players with otherwise similar characteristics. As Kahn (2000) documented, however, data from the early to mid-1990s generally offer much less support for salary discrimination against Blacks in the NBA (see, for example, Bodvarsson & Brastow, 1999;Dey, 1997;Gius & Johnson, 1998;Hamilton, 1997).…”
Section: Notesmentioning
confidence: 99%
“…We defined a player to be overpriced, if a team had paid too much for him, relative to his past performance, and other observable characteristics. To test this alternative explanation, we estimated a wage model of NBA salaries that followed the approach in earlier studies (e.g., Gius & Johnson, 1998;Berri, Brook, & Schmidt, 2007). However, analyzing the wages of more than 1'000 free agent signings, we did not observe any influence of social tie hiring on player wages.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether the influence on winning percentage was driven by systematic overpayment of tie-hirings rather than by suboptimal fit of players, we estimated a wage model of NBA salaries. Building on prior work in this area (e.g., Gius & Johnson, 1998;Berri et al, 2007), we analyzed the salaries of more than 1'000 free agent signings based on prior performance and player characteristics. As Berri et al (2007) showed that scoring is almost as predictive as any other performance measure that incorporates a wide range of playing statistics, we only included scoring to capture prior performance in a parsimonious way.…”
Section: Resultsmentioning
confidence: 99%